Influence of calcination on the morphology and crystallinity of titanium dioxide nanofibers towards enhancing photocatalytic dye degradation - Soo, Joshua Zheyan; Ang, Bee Chin; Ong, Boon Hoong (IOP Publishing, 2018)
The development of titanium dioxide (TiO2) nanostructures with superior morphology and crystallinity is crucial for the photocatalytic degradation of textile dyes. This study highlights the evolution in the morphology and crystallinity of electrospun TiO2 nanofibers using polyvinylpyrrolidone (PVP) support in relation to applied calcination temperature, and their influence towards the photocatalytic dye degradation performance of the material. Results showed distinct differences in the thermal decomposition patterns of (PVP) on the fiber surface and the inner core, where it is dependent on the presence of oxygen. These differences drastically affect the morphology of the obtained fibers especially its surface area and porosity. Crystallinity of the embedded TiO2 particles increases with higher calcination temperature which contributes to higher photocatalytic performance. Highly mesoporous nanofibers with crystalline anatase TiO2 particles, together with fiber diameter of 118.3 ± 6.30 nm and surface area of 72.3219 m2 g-1 are obtained at 500 °C. The combination of these properties produced the best photocatalytic dye degradation rate constant of 0.080 29 min-1 and 0.0543 min-1 for methylene blue and methyl orange respectively. The performance can be attributed to a combination of high particle crystallinity and fiber porosity and surface area.